The Prevalence and Severity of Carpal Tunnel Syndrome during Pregnancy - Javed Iqbal Khan, Sadia Dilawer, Sajad Ahmed, Akhtar Zaman, Raziullah, Ayesha Tahir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Carpal Tunnel Syndrome (CTS) is a common condition during pregnancy, characterized by the compression of the median nerve in the wrist. This leads to symptoms such as tingling, numbness, and pain in the hand and fingers. The prevalence and severity of CTS among pregnant women remain crucial areas of research to better understand the impact of pregnancy on peripheral neuropathies. Objective: To assess the prevalence and severity of Carpal Tunnel Syndrome in pregnant women and to identify potential risk factors associated with its onset and progression. Methods: A cross-sectional study was conducted on 220 pregnant women. Data on demographic characteristics, obstetric history, and CTS symptoms were collected. Physical examinations and electrodiagnostic tests were performed to confirm the diagnosis of CTS. Results: The prevalence of CTS was found to be 42% of the study population. The severity of CTS was classified as mild in 34%, moderate in 32%, and severe in 34%. A significant correlation was observed between the severity of CTS and factors such as advanced maternal age, obesity, and prolonged use of hands for repetitive tasks. Conclusion: Carpal Tunnel Syndrome is highly prevalent during pregnancy, and its severity varies significantly. Early diagnosis and management, including conservative treatments and lifestyle modifications, are recommended to mitigate the impact of this condition on the well-being of pregnant women. Keywords: Carpal Tunnel Syndrome, Pregnancy, Prevalence, Severity, Risk Factors, Electrodiagnostic Testing, Obstetric History, Physical Examination